Generation of two-photon States with an arbitrary degree of entanglement via nonlinear crystal superlattices. - U'Ren, AB; Erdmann, R; de la Cruz-Gutierrez, M; Walmsley, I (2006)
We demonstrate a general method of engineering the joint quantum state of photon pairs produced in spontaneous parametric down-conversion. The method makes use of a superlattice structure of nonlinear and linear materials, in conjunction with a broadband pump, to manipulate the group delays of the signal and idler photons relative to the pump pulse, and realizes photon pairs described by a joint spectral amplitude with arbitrary degree of entanglement. This method of group-delay engineering has the potential of synthesizing a broad range of states including factorizable states crucial for quantum networking and states optimized for Hong-Ou-Mandel interferometry. Experimental results for the latter case are presented, illustrating the principles of this approach.